Employees’ Perspectives on Leadership in Times of Crises in Romanian SMEs - Saseanu, Andreea Simona; Grosu, Raluca Mariana; Ghita, Simona Ioana; Ene, Andreea Bianca (Transformations In Business & Economics, 2025)
The paper addresses the perception of employees in Romanian small and medium-sized enterprises (SMEs) regarding the way their leaders approached them during crisis periods, focusing on an important recent disruptive moment, respectively the COVID-19 pandemic. The analysis tackles employees’ perceptions about the support they received, their access to motivation measures, engagement, satisfaction, and degree of trust in the company during the pandemic. Based on a questionnaire-based survey, the paper advocates that during crisis periods, focusing on the COVID-19 pandemic, employees in consultative and/or collaborative-led SMEs benefited from greater support from their leaders, were more involved in the motivation measures implemented by their leaders and were more confident in their enterprises, compared to employees in autocratic led SMEs. On the contrary, employees’ engagement and satisfaction were not influenced by the practised leadership style in the analysed SMEs during the pandemic.